Research on the mechanisms of plant bioactive metabolites in anti-skin aging and future development prospects - Wang, Haoran; Zheng, Jinyv; Cao, Shikui; Lv, Jingwei (Frontiers in Pharmacology, 2025)
With the accelerated pace of modern life and the influence of various environmental factors, skin aging has become a widespread health and aesthetic concern worldwide. Therefore, there is an urgent need for safe, effective and cost-efficient options for the prevention and treatment of skin aging. Researchers have been actively exploring anti-skin aging metabolites that can replace synthetic chemical agents. In recent years, natural plant bioactive metabolites isolated from plants have been considered as good alternatives and have been favored by an increasing number of researchers due to their rich content of bioactive metabolites and low side effects. Botanical bioactive metabolites have become a focal point in the field of anti-aging skincare due to their effectiveness in alleviating visible signs of skin aging and their potential to enhance the overall health of the skin. We collected relevant literature published between 2010 and 2025 using keywords such as “skin aging,” “plant bioactive metabolites,” “antioxidant,” “reactive oxygen species,” “matrix metalloproteinases,” “inflammation,” and others. This review describes skin aging, common plant (e.g., rice, ginseng, tea, etc.) bioactive metabolites and their efficacy and mechanism of action in delaying skin aging. In addition, the development potential and future trends of botanical bioactive metabolites are explored with the aim of providing a more holistic approach to skin aging care and offering valuable insights into the use of botanical bioactive metabolites as important metabolites in the formulation of anti-aging products.